1995
DOI: 10.1016/0167-5877(95)00498-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with seropositivity to porcine respiratory coronavirus in Danish swine herds

Abstract: Serolo,Eical screening of swine herds in 1984indicated that porcine respiratory coronavirus (PRCV) had been introduced into Denmark. To determine risk factors associated with the introduction of PRCV, a cross-sectional study of 408 Danish swine herds was carried out between May 1985 and June 1986. The association between herd-PRCV serological status and possible risk factors, obtained from a field questionnaire, was assessed by unconditional maximum likelihood logistic regression. An increasing herd size, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
(21 reference statements)
0
7
0
2
Order By: Relevance
“…The natural logarithm of the number of tested pigs per visit in a farm was associated with an increased ASFV seropositivity (Table 2). However, a logistic regression coefficient for ln(NTEST) p = 1 suggested that the risk of infection for a single animal was not affected by herd size (Willeberg et al, 1994;Flori et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The natural logarithm of the number of tested pigs per visit in a farm was associated with an increased ASFV seropositivity (Table 2). However, a logistic regression coefficient for ln(NTEST) p = 1 suggested that the risk of infection for a single animal was not affected by herd size (Willeberg et al, 1994;Flori et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Even for herds not introducing pigs and with limited contacts with other herds, there is empirical evidence that large swine herds are at increased risk of airborne introduction of viral diseases. For example, for infections such as PRCV and PRV (for which airborne transmission in Denmark has been reported), an increased risk of infection was evident in large herds (Henningsen et al, 1988;Christensen et al, 1990;Flori et al, 1995). In addition, the authors of these three studies found that a natural logarithmic transformation of herd size was the best formulation of the independent effect of herd size on the odds of positive PRCV or PRV status.…”
Section: Introduction Of Infectious Agents Transmitted By Airborne Romentioning
confidence: 99%
“…A discussion of herd size measures would be incomplete without reference either to herd (and pig) density in an area, which might also be positively correlated with herd size, or to pig stocking density within herds. Greater herd (and pig) density may be confounded with larger herd size at least in some countries, such as Denmark (Flori et al, 1995), and therefore might in part explain the reported herd-size effects. The importance of considering the density of infected herds or pig density on an area basis in addition to herd size as risk factors for pseudorabies was recognized in at least five studies (Austin et al, 1993;Leontides et al, 1994aLeontides et al, , 1995Boelaert et al, 1999;Maes et al, 2000).…”
mentioning
confidence: 99%
“…But, unless the upper layer of the straw bedding is kept fresh and dry, the strength of the horn will decrease because of the higher water content (Kroneman et al, 1993). Furthermore, slatted floors may be more stressful to pigs and indirectly, through a reduction in resistance, lead to an increased infection risk (Straw, 1986;Flori et al, 1995). This hypothesis may explain the lower risk for influenza A infections (Ewald et al, 1994) and stomach and intestine disorders (Christensen et al, 1995;Smith and McOrist, 1998) found in straw systems compared to slatted floors.…”
Section: Hygiene and Healthmentioning
confidence: 99%